Optical detection of metastatic cancer cells using a scanned laser pico-projection system. (11th February 2015) - Huang, Chih-Ling; Chiu, Wen-Tai; Lo, Yu-Lung; Chuang, Chin-Ho; Chen, Yu-Bin; Chang, Shu-Jing; Ke, Tung-Ting; Cheng, Hung-Chi; Wu, Hua-Lin
Abstract: Metastasis is responsible for 90% of all cancer-related deaths in humans. As a result, reliable techniques for detecting metastatic cells are urgently required. Although various techniques have been proposed for metastasis detection, they are generally capable of detecting metastatic cells only once migration has already occurred. Accordingly, the present study proposes an optical method for physical characterization of metastatic cancer cells using a scanned laser pico-projection system (SLPP). The validity of the proposed method is demonstrated using five pairs of cancer cell lines and two pairs of non-cancer cell lines treated by IPTG induction in order to mimic normal cells with an overexpression of oncogene. The results show that for all of the considered cell lines, the SLPP speckle contrast of the high-metastatic cells is significantly higher than that of the low-metastatic cells. As a result, the speckle contrast measurement provides a reliable means of distinguishing quantitatively between low- and high-metastatic cells of the same origin. Compared to existing metastasis detection methods, the proposed SLPP approach has many advantages, including a higher throughput, a lower cost, a larger sample size and a more reliable diagnostic performance. As a result, it provides a highly promising solution for physical characterization of metastatic cancer cells in vitro .